2004
DOI: 10.1038/sj.jhh.1001726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delapril–manidipine combination vs irbesartan–hydrochlorothiazide combination on fibrinolytic function in hypertensive patients with type II diabetes mellitus

Abstract: The aim of this double-blind, double-dummy, parallel group study was to compare the effects of delaprilmanidipine combination vs a irbesartan-hydrochlorothiazide combination on plasma tissue plasminogen activator (t-PA) and plasmogen activator inhibitor type I (PAI-l) activities in hypertensive patients with type II diabetes mellitus. After a 4-week run-in placebo period, 80 patients (37 male and 43 female), aged 41-65 years, were randomly allocated to an 8-week treatment with delapril 30 mg once daily or irbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
3
9
0
1
Order By: Relevance
“…Although the clinical relevance of diuretic-induced metabolic side effects is still debated, the choice of antihypertensive drugs, particularly in high-risk patients such as those with diabetes, should favor agents that do not worsen the global cardiovascular risk profile. No significant changes in metabolic parameters were observed in the patients treated with manidipine/delapril, which confirms previous observations (54,55).…”
Section: Discussionsupporting
confidence: 81%
“…Although the clinical relevance of diuretic-induced metabolic side effects is still debated, the choice of antihypertensive drugs, particularly in high-risk patients such as those with diabetes, should favor agents that do not worsen the global cardiovascular risk profile. No significant changes in metabolic parameters were observed in the patients treated with manidipine/delapril, which confirms previous observations (54,55).…”
Section: Discussionsupporting
confidence: 81%
“…25,26 Finally, the unfavourable effect of hydrochlorothiazide on fibrinolysis has previously been observed. 23 In the study by Mugellini et al, 18 it is of note that there were no statistical differences in blood pressure-lowering efficacy between both combinations of antihypertensive drugs with no changes in the whole study period. This feature is especially important in diabetic patients where the treatment of cardiovascular risk factors needs to be more intensive.…”
mentioning
confidence: 93%
“…17 In this issue of Journal of Human Hypertension, Mugellini et al, 18 report on the different effect of two combinations of recognised antihypertensive agents on the fibrinolytic system. Based on this well-conducted, double-blind, parallel group study, the combination of an angiotensin-converting enzyme (ACE) inhibitor and a calcium antagonist (delapril and manidipine) resulted in a greater improvement of the fibrinolytic function than the combination of an angiotensin receptor antagonist (ARB) and a diuretic (ibersartan and hydrochlorothiazide).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Other randomized clinical trials have demonstrated similar efficacy with regard to BP reduction with a manidipine/delapril combination compared with enalapril/HCTZ 15 or with irbesartan/HCTZ. 16 In addition to control of BP, inhibitors of the renin-angiotensin system appear to have independent effects on microalbuminuria. 17 The present data with the manidipine/delapril combination on microalbuminuria are consistent with previous studies of combination regimens that included an inhibitor of the renin-angiotensin system and a calcium channel blocker.…”
Section: Discussionmentioning
confidence: 98%